Exploring Traditional Dadiah Food as a Part of Cultural Identity and Sustainability in Minangkabau Tribe Tourism - Maulid, Amy; Ciptandi, Fajar (Jurnal Penelitian Pariwisata, 2023)
Traditional food is an intangible cultural heritage that has regional, specific characteristics, various kinds and types that reflect the natural potential of each region, so that Indonesia is not only said to be rich in nature, but also in all the diversity of culture and food that exists, but this does not rule out the possibility These traditional foods will experience extinction if their sustainability is not maintained, such as the conventional Dadiah food which originates from West Sumatra.Dadiah is a traditional yogurt from milk buffalo originating in Minangkabau,West Sumatra. Dadiah, as traditional food, needs to be preserved in modern society by providing elements of novelty but still taking into account the characteristics and fundamental values ​​that have been previously owned. This study aims to analyze the application of the innovation leadership pyramid in the traditional food product Dadiah in order to discover the elements of tradition in the traditional food product. This research uses a qualitative descriptive method by collecting data through observation, interviews, and literature study. The data obtained comes from factual conditions in the field when conducting research, so the data received will be analyzed using the innovation guide pyramid. It is hoped that the results of this research will be able to find new elements that can be applied to traditional dadiah food so that the traditional food remains preserved. Keywords: traditional food, dadiah, innovation guiding pyramid